Insights from practice A handbook for supervisors of modern doctorate candidates - Loxley, Andrew (My University, 2017)
The supervision of work-based research requires complex capabilities from supervisor(s) as they seek to: • address the diverse needs of a candidate operating at doctoral level within a work environment where their priorities are, in part at least, set by the needs of their organisation and work role; and • supervise the creation of knowledge at doctoral level. And yet there has to date been little study of these needs and no commonly accepted framework of practice for supervisors is currently available to draw upon. In moving beyond this state of the art the project team won Erasmus funding for a project whose objectives were to: • Access best practice in the supervision/advising of modern doctorates: • Identify the host/sponsoring organisation’s requirements from supervision (if any) and their contribution to it • Develop a framework of practice (supported by training resources) suitable for modern doctorates • Disseminate this best practice framework to all stakeholders • Produce a sustainable impact on supervisory practice throughout the EU. This handbook is one of the outputs for the project and its aim is to provide a quick reference guide for supervisors wishing to enhance their practice in the area of modern doctorates through accessing the rich experience of others in the field.
Keywords: Research supervision; Continuing Professional Development; Education and Work; Postgraduate education policy; doctoral education; doctoral supervision